Analysis of Stakeholder’s Understanding of Green Roads Principles in Construction of Yogyakarta-Bawen Toll Road Section I - Setyaning, Larashati B'tari; Aziz, Umar Abdul; Barkah, Laeli Nikmatul (Universitas Muhammadiyah Yogyakarta, 2024)
Infrastructure plays a vital role in economic development. Apart from having a positive impact, infrastructure development also has negative impacts such as global warming and reduced availability of natural resources. Therefore, a sustainable approach must be applied in construction projects, especially road construction. Considering the lack of awareness regarding implementing sustainable construction, this research aims to analyze the level and differences in stakeholder understanding regarding green roads in the Jogja – Bawen Toll Road construction project (section 1). This research uses a quantitative approach which uses primary data as the main data. Primary data was obtained through filling out questionnaires by respondents consisting of owners, consultants and contractors involved in the Yogyakarta-Bawen Toll Road Project (section 1). Based on data analysis, it can be concluded that the owner and contractor understand all the principles of sustainable construction, while the consultant only understands social and environmental principles.